Leveraging AI to Enhance Representation of Marginalized Voices in English Poetry Curricula in Indonesia - Mendrofa, Melania Priska (IJEE (INDONESIAN JOURNAL OF ENGLISH EDUCATION), 2025)
This study investigates how Artificial Intelligence (AI) can enhance the representation of marginalized voices in English poetry curricula at Indonesian universities. The objective is to explore AI's potential to diversify the selection of poets, shifting away from the traditional dominance of Western literary figures. Using AI-based tools to analyze large-scale poetry collections, the study identifies both prominent and lesser-known poets from underrepresented communities. The findings reveal that AI can significantly increase inclusivity by broadening the range of poetic voices featured in the curriculum, thereby contributing to the decolonization of literary studies. These results suggest that AI has the capacity to transform English poetry education in Indonesia, promoting a more equitable and globally relevant literary experience.